Metastasis of Hepatocellular Carcinoma to the Esophagus: Case Report and Review - Harada, Jun-ichiro (Case Rep Surg, 2018)
A follow-up endoscopy in a 71-year-old Japanese man who had undergone a left lateral segmentectomy for HCC two years ago revealed an approximately 2 cm in diameter pedunculated polypoid mass in the middle part of the thoracic esophagus. Immunohistochemical staining of the endoscopic biopsy revealed a metastatic HCC esophageal tumor. As the patient's disease could be radically removed by preoperative examinations, we resected the metastatic esophageal tumor via right thoracotomy and esophagogastrostomy reconstruction. Histological examination of the resected specimen revealed that the esophageal tumor was compatible with a HCC metastasis. This is an extremely rare case of a solitary metastasis to the esophagus from HCC in the literature.